Desarrollo de actividades didácticas multimedia complementarias para el software educativo como apoyo didáctico en el área de estudios sociales del nivel de educación general básica, enmarcado a los hechos históricos, geográficos y educativos del cantón Guabo de la provincia de El Oro - Alverca Villalta, Bagner Jairo (2016)
This research paper called "EDUCATIONAL DEVELOPMENT ACTIVITIES ADDITIONAL MULTIMEDIA EDUCATIONAL SOFTWARE FOR TEACHING AS SUPPORT IN THE AREA OF SOCIAL STUDIES GENERAL BASIC EDUCATION LEVEL, framed historical facts, GEOGRAPHIC AND EDUCATION OF CANTON GUABO THE PROVINCE GOLD ", aims to serve students in the teaching - learning process of the subject of Social Studies, as an innovative teaching tool that will motivate them to recover their cultural identity and get real learning time as regards historical facts, geographical and educational Canton El Guabo. Therefore this research work a solution to the lack of educational multimedia activities for educational software as a teaching support in the area of Social Studies highlighting the historical, geographical and educational events of El Guabo Canton arises. From the geographical point of view the investigation is physically framed in Region 7, in the province of El Oro, El Guabo Canton, schools are: Bolivia Murillo Serrano, Manuel Serrano, Zoila Ugarte de Landivar. To determine the requirements of teachers and students in the area of Social Studies conducted an interview teachers and verified that the environment is suitable for the use of teaching material. Through the methodology of Alvaro Galvis an adequate structure of the educational activities are conducted and by the Jclic, Cuedernia and eXeLearning tools, educational activities developed content with greater difficulty learning according to the view of teachers, once completed they were socialized and evaluated using an evaluation sheet.